Mediation Role of Affective Commitments The Effect Of Organizational Justice on Innovativeo Behavior : Survey at SMK 01 Muhammadiyah Yogyakarta - Hairani, Hairani; Tjahjono, Heru Kurnianto; Wahyuningsih, Rr. Sri Handari (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2023)
This study examines the effect of distributive justice, procedural justice, and interactional justice on affective commitment and innovative behavior. The sample of this study was 127 teachers of SMK 01 Muhammadiyah Yogyakarta. The research method uses the SEM method and uses the AMOS IBM SPSS analysis tool. The results showed that distributive justice, procedural justice and interactional justice had a positive effect on innovative behavior either directly or through the mediation of affective commitment variables. A high level of distributive justice, procedural justice, and interactional justice will increase the innovative behavior of teachers. However, the effect of distributive justice, procedural justice, and interactional justice on innovative behavior will be higher through affective commitment variables